Educação, trabalho e formação do trabalhador de nível técnico: políticas públicas sobre educação profissional em Uberlândia-MG - Ramos, Alícia Felisbino (2010)
This work is inserted into the History and Historiography of the Graduate Program in Education at Universidade Federal de Uberlândia and it aimed to examine government policies directed to the work and education world, concerning the structure and functioning of the Professional Education of the technical courses in Brazil and Uberlândia-MG. It is considered that the educational laws present the embodiment of political perspectives which reflect the demands of capital in the world of work. However, the observation of historical professional network showed by governments reveals in its foundation basically to serve the same purpose at the time of its creation in the country a century ago in 1909, when the government's justification was the need to provide the proletarian class of way to guarantee their survival. We used secondary research, as well as literature and field research to collect the data used to benefit analysis. It showed that it historically, the center line of policy for vocational education has been organized around the relationship between capital and work, attempting to general interests of capital. For this reason, recent legislation maintains the logic of the structurally dualistic school. The challenges of facing the dichotomy problem require recognition of the dual task: preparing the citizen for the job market and to continue the study. It is a complex issue that goes beyond the pedagogical aspects, but refers to the policy determined by changes in the material basis of production. Our field research was conducted with 39 graduates of technical courses at the School Agrotécnica Federal de Uberlândia. This analysis showed the contribution of the School Agrotécnica Federal de Uberlândia to training of these graduates, we have also know the employment status of graduates and how the job market has received the newly trained workers. From the analysis we noticed that most of the graduates searched the School Agrotécnica Federal de Uberlândia not as a way to professionalization, but as way of reaching higher education more easily.